Julius Carl Ertel. Ein Hamburger Industrieller - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2017)
Julius Carl Ertel held a special position as director and later as sole owner of a copper smelter in the commercial and trading city of Hamburg. Born in Wroclaw, he came to the Hanseatic city at the age of 26. Together with Rudolph Bieber, he founded Ertel, Bieber & Co. in 1872. The company had its facilities in the middle of the harbour area. However, Ertel gained its decisive importance through the extensive connections he made with numerous other companies throughout Germany. In the supervisory boards of these companies, he played an active role in building up the expanding economy of the Gründerzeit. Ertel was not a man who pushed himself into the foreground. This early donor of the Hamburgische Wissenschaftliche Stiftung acted as a networker in the modern sense of the word